THE ROLE OF ALGORITHMS IN APPLYING OCCUPATIONAL RISK ERGONOMICS TO ACHIEVE “LOST SAFETY” ACCORDING TO ULRICH BECK’S MODEL - Sali Mohammed, (International Journal of Innovative Technologies in Social Science, 2025)
This research examines the role of algorithms and artificial intelligence techniques in enhancing occupational safety across various work environments. It focuses on how these algorithms are utilised to analyse and predict occupational risks with greater accuracy, thereby contributing to the reinforcement of preventive measures and the reduction of accidents. The study also addresses the challenges associated with the application of these technologies, such as data heterogeneity and the capacity to predict emerging risks. Furthermore, the research discusses the significance of Ulrich Beck's model in deepening the understanding of social risks and its practical applications in the field of occupational safety. In conclusion, the research presents a set of recommendations to improve occupational safety through the effective integration of algorithms and modern technologies.